Red Ginger Essential Oil (Zingiber officinale var. Rubrum) as a Biolarvicide in the Control of Aedes Aegypti Mosquitoes - Denai Wahyuni; Wulan Sari; Jasril Jasril; Jufrizal Syahri (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Synthetic larvicides are often used to control Aedes aegypti mosquitoes, but they are detrimental to humans, the environment, and the occurrence of resistance. The purpose of the study was to determine the influence and effectiveness of red ginger essential oil (Zingiber officinale var. Rubrum) as the biolarvicide of Ae. Aegypti and the most effective concentration (LC50). A total of 25 instar 3 larvae with concentrations of 200, 400, 600, and 800 ppm and K+(temephos), K-(aquaade), four repetitions every 30 minutes of observation for 3 HSPs. The results of the study showed that red ginger essential oil affected the death of Ae. Aegypti larvae. There was a significant difference in mortality rates between concentrations (Kruskal-Wallis test, p = 0.001). Likewise, there was a moderate but significant correlation between concentration and mortality (Spearman correlation: r = +0.503, p = 0.001). The probit analysis, LC50 was 257.89 ppm, most effectively influencing mortality in Ae. Aegypti larvae based on LC50. Red ginger essential oil (Zingiber officinale var. Rubrum) is effective and effective as a bio-larvicide to control Ae. aegypti so that it can reduce dengue fever cases.